Hepatoprotective Effect of Mangosteen Peel Extract on Borax-Induced Male Rats - Yunita Satya Pratiwi; Bambang Wirjatmadi; Mangestuti Agil; Merryana Adriyani; Supriyadi Supriyadi (International Journal of Public Health Science (IJPHS), 2016)
The aim of this study was to determine the hepatoprotective effect of mangosteen peel extract (MPE) on borax-induced male rats. Hepatoprotective effect is represented by the variables of liver weight, SGOT (Serum Glutamic oxaloacetic transaminase) and SGPT (Serum Glutamic Pyruvate Transaminase). The true experimental study used randomized separated pretest-posttest control group design. MPE was made with 50% ethanol and 0.5% carboxymethyl cellulose-sodium (CMC-Na) stabilizer solutions. Studied groups included three control groups (positive, negative pretest and posttest) and three experimental groups (MPE dose of 200 mg/kg, 400 mg/kg and 600 mg/kg rats body weight (BW)). Samples consisted 36 male rats. The length of intervention was 16 days by providing borax, and then MPE was started on day 3 (in 3 experimental groups). Results showed that up to 16th day the SGOT tended to decrease (α <0.05), while the SGPT levels was stable, and so was the liver weight. Thus, up to day 16 the MPE was generally able to provide hepatoprotective effects mainly based on the variable SGOT in doses of 200 and 400 mg/kg. It has been proved that liver function of the rats was still relatively normal. This is in relations to the antioxidant potential of the MPE polyphenols.